Review of X-ray phase contrast imaging techniques and propagation based imaging using a Benchtop Microfocal Source - Bradley, David; Gondogdu, Ozcan; Jenneson, Paul; Nirgianaki, Eleftheria; Elna Herawati Che Ismail (penerbit ukm, 2007)
Currently, the basis for standard clinical X-ray radiography is absorption, tracking attenuation of radiation when X-ray beams pass through a particular part of the body. The fundamental interaction processes are dependent on variations in the atomic number and density of the target medium; consequentially radiographic contrast can be poor, particularly in regard to soft tissue imaging. Over the past several years considerable interest has been paid to utilising phase properties of the X-ray field to enhance radiographic Jurnal Sains Kesihatan Malaysia 5 (1) 2007: 1-162 contrast in challenging circumstances, particularly with respect to soft-tissue imaging. Surrey is among an increasing number of institutes in which a programme of investigation of phase contrast X-ray imaging has been established. We briefly review some basic ideas in X-ray phase contrast imaging and then examine the radiographic contrast enhancement that can be obtained, use being made of the method of free-space propagation and investigating a number of test objects, including biological samples. The equipment used at Surrey is relatively simple, comprising of bench-top X-ray tubes with focal spot sizes from a few microns up to 100 microns and a position sensitive 12 bit CCD detector.